Duplex detection of avian and chicken using common primer-pcr in processed meat products - Hanapi, Ummi Kalthum; Mohd Desa, Mohd Nasir; Mohamad, Nurhidayatul Asma; Khairil Mokhtar, Nur Fadhilah (GADING Journal of Science and Technology, 2024)
Meat fraudulent practice has been proven to damage the quality of the food and consumer’s health. Being widely available at a lower cost, chicken meat has been frequently used as a meat substitute in meat-based food products. As a solution, a duplex polymerase chain reaction (PCR) assay employing a common primer coupled with a unique adapter sequence was developed for simultaneous chicken-specific and avian universal detection. The assay targeting 322 and 209 bp of melanocortin 1 receptor (MC1R) gene sequence was optimized with high specificity against a range of avian and meat species and a high limit of detection (LOD) of 0.01 ng. Across 42 commercial meat products tested, chicken meat was detected in seven non-avian samples, where only two of them declared the presence of chicken meat on the label. The practical duplex PCR assay can be potentially applied for routine practice in qualitative investigation of contamination or adulteration in processed meat products.